Specificities of victimization in Serbia and its importance for truth and reconciliation process - Nikolić-Ristanović Vesna Ž. (Temida)
In this paper the author analyses specificities of the situation in Serbia relevant for the discussion about possibilities of truth and reconciliation. These specificities include: the connection between past and present, the complexity of victimization and present political context. Special emphasis is put on the history of denial of crimes, multiple victimization and misuse of victimization of one’s own people as characteristics of entire Balkan region.